2006
DOI: 10.1016/j.ejcts.2006.06.032
|View full text |Cite
|
Sign up to set email alerts
|

A single 24F Blake drain after wedge resection or lobectomy: a study on 100 consecutive cases

Abstract: Postoperative courses after standard thoracic procedures using a single 24F Blake drainage appear similar to that accounting after a classical semi-rigid drainage. Such single drainage may appear now as an acceptable option. The flexible quality of the drain, its reduced caliber, and the character unique of the drainage, may contribute to improve comfort of the operated patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 4 publications
2
24
0
Order By: Relevance
“…Factors that may have caused bias of the results, such as the use of coagulation‐affecting drugs and neoadjuvant therapy, were eliminated during patient enrollment. Wedge resection cases were also excluded to eliminate the bias caused by different procedures . Propensity score matched analysis was applied to overcome any bias that may have been caused by imbalances in patient age and tumor stage.…”
Section: Discussionmentioning
confidence: 99%
“…Factors that may have caused bias of the results, such as the use of coagulation‐affecting drugs and neoadjuvant therapy, were eliminated during patient enrollment. Wedge resection cases were also excluded to eliminate the bias caused by different procedures . Propensity score matched analysis was applied to overcome any bias that may have been caused by imbalances in patient age and tumor stage.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have been published comparing the use of one chest tube with the use of two chest tubes for thoracic drainage after pulmonary lobectomy, but most of these were observational studies (Alex et al 2003;Kejriwal and Newman 2005;Icard et al 2006), and there have so far only been three reports of randomized controlled trials (Gomez-Caro et al 2006;Pawelczyk et al 2007;Okur et al 2009). The results of the randomized trials revealed that proper extension of the residual lung could be achieved even with one chest tube.…”
Section: Discussionmentioning
confidence: 99%
“…We read with great interest the article by Icard and coworkers on the use of a single 24 F Blake drain (Johnson & Johnson, Somerville, NJ) [1]. We first reported the use of Blake drains for drainage of pleural cavity in patients undergoing thoracotomy [2].…”
mentioning
confidence: 97%